A Discussion on the Factors Affecting Organizations and Management Performance: A Lesson Learned for Business Students - Channarika, Kan; Mardy, Serey (MultiTech Publisher, 2024)
All managers these days search for the variables that impact individual or organizational outcomes such as productivity and performance. Organizational culture is among these variables. A growing number of people recognize organizational culture as a resource that businesses may leverage to boost productivity. Corporate culture is a crucial idea, yet it can be difficult to articulate in precise terms. In order to better understand how the term